Licit Substance Use and Premenstrual Syndrome Symptom Severity in Female College Students - Kathryn Polak; Pamela Nora; Bridget Perry; Caitlin Martin; Pam Dillon; Leroy Thacker; Sarah Nance; Susan Kornstein; Dace Svikis (Mary Ann Liebert, 2022)
Introduction: Premenstrual syndrome (PMS) affects the majority of women and is characterized by physical, behavioral, and mood symptoms, which can have a profound impact on quality of life. PMS symptoms have also been linked to licit substance use. This study examined the relationships between daily/problem use (DPU) of caffeine (Caf+), alcohol (Alc+), and tobacco (Cig+) and PMS symptomology in a sample of college women. Methods: Participants (N?=?196) completed an anonymous one-time health survey. Demographic, PMS symptomatology, and DPU of licit substance variables were examined. Independent t-tests compared PMS symptom scores in women with and without Caf+, Cig+, and Alc+ use. One-way analysis of variances examined the associations between PMS symptom severity and number of DPU-positive substances. Results: PMS subscale severity (pain [F(2,190)?=?4.47, p?=?0.013], affective [F(2,192)?=?8.21, p?<?0.001], and water retention [F(2,191)?=?13.37, p?<?0.001]) and total PMS symptom severity [F(2,189)?=?10.22, p?<?0.001] showed a dose response effect, with the number of licit substances with DPU significantly associated with PMS symptom severity. Conclusions: This study findings provide important new information about the relationship between PMS symptoms and at-risk substance use. These are cross-sectional data, however, and affirm a need for longitudinal research to better understand the associations, with a focus on potential benefits of education and intervention.